Environmental and population externalities - Jöst, Frank; Quaas, Martin F. (Environment and development economics, 2010)
We analyze the external effects that arise in the decisions of firms on polluting emissions and in the decisions of parents on the number of births in an optimal control model with three stock variables representing population, economic capital, and pollution. We distinguish two different types of households, which represent opposite ends of a spectrum of potential familial structures: ‘dynastic households’, in which the family sticks together forever and ‘micro-households’, in which children leave their parent's household immediately after birth. We show that the decision of parents on the number of births involves an externality that is qualitatively different for both types of familial structure. Hence, population policy should be different, according to the type of household. A first best result may be obtained in the case of dynastic households if an appropriate tax on the household size is applied, or, in the case of micro-households, if an appropriate tax on children is applied.
Published online by Cambridge University Press: 21 May 2009
Gesehen am 28.08.2023